Korelasi Konsep Nafkah sebagai Wujud Ketahanan Keluarga di Desa Sindangsari - Galby Silvia Rachmah; Moh. Mahrus; Khairuddin Nasution (CV. Creative Tugu Pena, 2024)
Family resilience is a measuring tool for measuring family achievements in carrying out roles, functions and responsibilities in order to achieve the welfare of family members. Socio-economic changes have changed the traditional roles of husband and wife. Economic instability is a big challenge in fulfilling family livelihoods. Many women now work and contribute significantly to the family income. Determining the relationship between the application of the concept of livelihood and the level of family resilience is the aim of writing this scientific research. The discussion in this scientific journal is the definition and concept of livelihood, factors that influence family resilience, and the impact of applying the concept of livelihood on family welfare. The research method used in this scientific journal uses literature study methods and reinforcement through informant interviews. The findings in this scientific journal state that implementing the concept of a balanced and effective living can significantly increase family resilience.